Seismic performance assessment and rating for a flat-slab RC core wall structure in Bucharest, Romania. (June 2021) - Pavel, Florin; Vacareanu, Radu; Marcu, Dragos
Abstract: This study focuses on the assessment of the seismic performance for a 12-story high reinforced concrete structure situated in Bucharest, Romania. The structural system is common for many newly built office buildings in Bucharest and it consists of a flat slab with columns and thick reinforced concrete core walls. The seismic performance of the structural system is evaluated using ground motions with considerable long-period spectral amplifications, that are characteristic to Bucharest area during large magnitude Vrancea intermediate-depth earthquakes. The building is the first office building having a flat slab structure with core walls designed for the seismic conditions of Bucharest which is evaluated according to US Resiliency Council criteria and according to recent criteria proposed by Italian Guidelines. The results of the seismic rating show that it can be classified as a 3-stars for the safety criterion and as a 4-stars one for both the recovery time and repair cost criteria according to US Resiliency Council criteria. Moreover, the building can be graded as a class A one based on the criteria from the Italian Guidelines.